Silver(I)-mediated oxidation/cyclization of acrylamides with alkyl trifluoroborates. Issue 4 (16th February 2021) - Ding, Siyi; Ren, Huaping; Zhu, Min; Ma, Qiang; Miao, Zongcheng; Li, Pengfei
Abstract: A mild silver-mediated oxidative cyclization of acrylamides has been developed by using alkyl trifluoroborates as radical precursors. It proceeds through a tandem radical addition/cyclization process, in which two new carbon-carbon bonds were formed. This protocol allows reliable and practical access to build the skeleton of 3, 3-disubstituted oxindoles in moderate yields, the readily available starting reagents, broad substrate scope and mild reaction conditions are the characteristic features of this protocol. Graphical Abstract: